Ethics of experimentation. Ethical review of experimental research protocols - MARINOU (Κ. ΜΑΡΙΝΟΥ), K.; DONTA (Ι. ΔΟΝΤΑ), I. (Journal of the Hellenic Veterinary Medical Society, 2017)
This paper describes a set of principles for the conduct of ethical review regarding experiments carried out on laboratory animals, which is important to be maintained from researchers throughout the whole process, from the initial design of the experimental protocol up to the publication of results in a peer-reviewed journal. Animal use should be justified after thorough examination of the existing validated alternative methods. The ethical review of experimental protocols will very soon become obligatory as the revision of the European Directive 86/609/EEC, regarding the protection and welfare of experimental animals, and the process will be clearly defined. In Greece several ethical committees have already been established in academic and research institutions that review applications submitted by researchers who have to prove that they are aware of all ethical aspects of animal experimentation, including a harm/benefit analysis where special attention to the severity of the procedure is given. Ethical committees are responsible for the initial ethical evaluation of research protocols that plan to use laboratory animals and for ensuring that animal welfare considerations are applied. Ethical committees may comprise experts from various scientific fields, among which the participation of a veterinarian specialized in Laboratory Animal Science and Medicine is considered to be essential. The ethical evaluation process needs to become a vital necessity for all researchers wishing to deal with Laboratory Animal Science and biomedical research.